الكتابة عند ادوارد سعيد - سالي, خيرة (مكتبة كلية الأدب العربي والفنون, 2023)
يرى إدوارد سعيد أن الكتابة هي وسيلة اتصال التي تمكن الإنسان من تدوين أرائه وأفكاره ومشاعره في مجالات الحياة المختلفة، ووضح ذلك في كتابه "العالم والنص والناقد"، جاء به سعيد ليتجاوز ذلك النقد التقليدي الذي يضم الأدب فقط، بل كل أشكال المعرفة التي ينتجها الإنسان بالإضافة إلى تمييزه بين مختلف المفاهيم من بينها العالم والنص والناقد وعلاقة كل مفهوم بالآخر، وبينا أيضا القضايا المطروحة في الكتاب. وفي نهاية دراستنا توصلنا لأهم النتائج أهمها تعميق ادوارد سعيد فكرته الأساسية عن ترابط النص بالعالم والناقد . : العالم، النص، الناقد، الكتابة، النقد الثقافي Summary Edward Said believes that writing is a means of communication that enables a person to write down his opinions, ideas and feelings in the various fields of life, and this was explained in his book "The World and the Text and the critic", which Said brought him to transcend that traditional criticism that includes literature only, Rather, all forms of knowledge that a person produces in addition to his distinction between the various concepts, including the world, the text, the critic, and the relationship of each concept to the other, and also showed the issues raised in the book. At the end of our study, we reached the most important results, the most important of which is the deepening of Edward Said his basic idea of the coherence of the text with the world and the critic. Keywords : world, text, critic, writing,Cultural critism.
Keywords: العالم، النص، الناقد، الكتابة، النقد الثقافي